2019
DOI: 10.1021/acs.inorgchem.9b01466
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Optical Properties in an Isomorphous Family of Multinary Iodido Pentelates

Abstract: Multinary organic−inorganic metal halide materials beyond the perovskite motif can help to address both fundamental aspects such as the electronic interactions between different metalate building units and practical issues like stability and ease of preparation in this new field of research. However, such multinary compounds have remained quite rare for the halogenido pentelates, as the formation of simpler side phases can be a significant hindrance. Here, we report a family o f f o u r n e w m u l t i n a r y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 97 publications
2
13
0
2
Order By: Relevance
“…Typical iodido plumbates with molecular anions have band gaps in the range of 2.9–3.2 eV [59] . Iodido antimonates and bismuthates with mononuclear anions display band gaps of 2.2 and 2.1 eV, respectively [60] . This suggests a significant electronic interaction between the EI 6 and PbI 6 units in 1 and 2 , which we elucidate with quantum chemical methods (see below).…”
Section: Figurementioning
confidence: 83%
“…Typical iodido plumbates with molecular anions have band gaps in the range of 2.9–3.2 eV [59] . Iodido antimonates and bismuthates with mononuclear anions display band gaps of 2.2 and 2.1 eV, respectively [60] . This suggests a significant electronic interaction between the EI 6 and PbI 6 units in 1 and 2 , which we elucidate with quantum chemical methods (see below).…”
Section: Figurementioning
confidence: 83%
“…On the other hand, in our recent works we showed that the formation of polyhalide–halometates is a general feature for p-block elements including bismuth­(III), , antimony­(V), and tellurium­(IV), and these compounds demonstrate fascinating structural diversity: dihalogen or, more rarely, polyhalogen fragments connect halometalate anions into one-dimensional (1D), two-dimensional (2D), or even three-dimensional (3D) supramolecular associations. Apart from the fundamental importance of these findings in terms of inorganic (interestingly, these studies coincided with great progress in the research of polyhalides per se ), supramolecular, and structural chemistry, an additional argument in favor of further investigations in this area is related to halometalate-based solar cells, which represent one of the “hot topics” in modern materials science. Indeed, it can be assumed that the presence of di- or polyiodide units in the structure can be favorable in terms of relevant physical properties. On the one hand, it causes additional noncovalent interactions, increasing dimensionality and (likely) resulting in enhanced charge transfer; on the other hand, it is expected to decrease the optical-band-gap values.…”
Section: Introductionmentioning
confidence: 92%
“…Typische Iodidoplumbate mit molekularem Anion weisen Bandlücken im Bereich von 2,9–3,2 eV auf [59] . Iodidoantimonate und ‐bismutate mit mononuklearem Anion zeigen Bandlücken von 2,2 beziehungsweise 2,1 eV [60] …”
Section: Figureunclassified
“…[59] Iodidoantimonate und -bismutate mit mononuklearem Anion zeigen Bandlücken von 2,2 beziehungsweise 2,1 eV. [60] Dies deutet auf eine signifikante elektronische Wechselwirkung zwischen den EI 6 -und PbI 6 -Einheiten in 1 und 2 hin, welche wir mit quantenchemischen Methoden näher untersuchen (siehe unten). Der Einbau von Bismutatomen reduziert die Bandlückenenergie um 0,14 eV.…”
Section: Zuschriftenunclassified